A Study on the Shoulder of Cell Survival Curve in Relation With Repair Capacity of Cells After Being Irradiated - Saleh, A. Z (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Aim:- to show  that not all survival  curves without shoulder  are not able to repair or have lost the ability for the accumulation of sublethal damage.Background:-  the shoulder  of the survival  curve  is considered  as aregion of accumulation  of sublethal  damage also as an indicator  for cell capacity to repair. The size can be influenced by the change ofthe slope of the linear portion of the survival curve.Results:- we have shown  that a survival curve with  shoulder size of1.5 Gy can be a straight line  when the slope of the  exponential part is changed  so  the  same  region  of  the  low  dose  of  the same  survival fraction  can  show  shoulder  at  one  time  and  with  no  shoulder  at another.Conclusion:-  we have shown  that in some cases cell survival  curvecould Jose its shoulder without the necessity of losing its capacity for repair.